2013
DOI: 10.1590/s1677-5538.ibju.2013.02.16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute administration of sildenafil to rats with detrusor overactivity induced by chronic deficiency of nitric oxide

Abstract: Purpose: Recently, the effect of phosphodiesterase inhibitors (PDE5i) in the lower urinary tract symptoms (LUTS) associated to benign prostatic hyperplasia have been studied thoroughly. However, it remains unclear how the PDE5i improve LUTS. Therefore, the aim of the present study was to evaluate the potential of acute administration of the PDE5i sildenafil to improve detrusor overactivity (DO) induced by N ω -nitro-L -arginine methyl ester hydrochloride (L-NAME), an nitric oxide sinthase (NOS) inhibitor, in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
3
5
0
Order By: Relevance
“…Thus, PDE5i increasing cGMP can probably explain the reduction in VT (decrease urethral resistance) and MC (relaxation of detrusor) observed in this study. This finding was comparable to other study that concluded that acute administration of sildenafil decreases the number of MC (18). As tadalafil did not decrease detrusor pressure (LP or PP) become +P < 0.05 comparing L-NAME with control; *P < 0.05 comparing Tadalafil and Tamsulosin/Tadalafil groups with L-NAME.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Thus, PDE5i increasing cGMP can probably explain the reduction in VT (decrease urethral resistance) and MC (relaxation of detrusor) observed in this study. This finding was comparable to other study that concluded that acute administration of sildenafil decreases the number of MC (18). As tadalafil did not decrease detrusor pressure (LP or PP) become +P < 0.05 comparing L-NAME with control; *P < 0.05 comparing Tadalafil and Tamsulosin/Tadalafil groups with L-NAME.…”
Section: Discussionsupporting
confidence: 88%
“…Increase in NVC and MC in experimental in vivo studies have been associated with DO (18). This finding was also similar to an organ bath study that evaluated bladder of rats submitted to chronic NO deficiency induced by daily administration of L-NAME.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Micturition frequency was measured considering the number of micturition cycles within 30 minutes. Threshold pressure was defined as the pressure immediately before micturition (8). Bladders of mice used for cystometry were not used in the other experiments.…”
Section: Methodsmentioning
confidence: 99%